A cold plasma-activated in situ AgCo surface alloy for enhancing the electroreduction of CO2 to ethanol. Issue 17 (17th April 2020) - Zhang, Qiang; Tao, Shuihui; Du, Jun; He, Anbang; Yang, Yong; Tao, Changyuan
Abstract : With regard to using the electric energy generated by renewable sources, the CO2 electroreduction reaction (CO2 RR) for the production of fuels is helpful for creating an artificial carbon cycle. Abstract : With regard to using the electric energy generated by renewable sources, the CO2 electroreduction reaction (CO2 RR) for the production of fuels is helpful for creating an artificial carbon cycle. Herein, for the first time, we prepared in situ AgCo surface alloy electrocatalysts at room temperature by the cold H2 -plasma activation method; these electrocatalysts showed high activity for the CO2 RR to ethanol with an excellent faradaic efficiency of ethanol (72.3%) and current density (7.4 mA cm −2 at −0.80 V). Based on experiments and DFT calculations, this high intrinsic activity was attributed to the selective suppression of hydrogen evolution and C1 production due to the distortion of the Ag lattice induced by the formation of a 111Ag + Co surface alloy to reduce the energy barrier for *CO2 δ − formation; this increased the coverage of CO* and resulted in a C–C coupling reaction to form *OC–CO* on Ag atoms (CO* pool sites), which was further converted to CH3 CH2 OH. Thus, this result showed that promoting the Ag surface with small amounts of Co is a promising way to improve ethanol selectivity during the CO2 RR.